Constructing Religion-Based Sexual Violence: Religious Authority and Women’s Resistance in Bidaah (2025) - Yunda Fithriyah; Deni Yatri; Nurul Hasna Khoirunnisa; Leonardus Dapa Dey; Liana Septiyanti (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
Religion-based sexual violence in pesantren represents a critical form of gendered violence, particularly when religious authority is mobilized to legitimize sexual exploitation. The Malaysian religious drama series Bidaah (2025) depicts the manipulation of Islamic teachings and religious authority in sexual violence against female students. This study examines how the series represents religion-based sexual violence and reconstructs women’s critical consciousness and resistance. Employing a qualitative descriptive design, the study analyzes scene dialogues as primary data, complemented by scholarly articles, books, research reports, and credible news sources as secondary data. Drawing on Stuart Hall’s constructionist theory of representation, the study applies qualitative textual analysis to examine how religious meaning, authority, and sexual violence are discursively constructed. The findings show that sexual violence is represented through the strategic reconstruction of religious discourses, particularly obedience, religious devotion, “spiritual wife,” and “spiritual marriage,” which normalize religious authority and reframe sexual abuse as religious devotion. Simultaneously, the series portrays women’s critical consciousness through questioning, resistance, and reinterpretation, reflected in recurring expressions such as “report,” “evidence,” and “fear.” The study demonstrates that Bidaah not only exposes how religious discourse can legitimize sexual violence but also constructs women’s resistance as a process of reclaiming interpretive agency and challenging the abuse of religious authority.